Adoption of CA technologies among Followers of Lead Farmers: How Strong is the Influence from Lead Farmers? - Monica Fisher; Stein T. Holden; Samson P. Katengeza (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
This study investigates how the Farmer-to-Farmer-Extension (F2FE) system with lead farmers and follower farmers influences adoption of Conservation Agriculture (CA) technologies in Malawi. Using data from 180 lead farmers and their 455 followers in central and southern Malawi, we assess the level of influence lead farmers have on their followers' familiarity with and adoption of CA. The main findings are that (a) lead farmers have significant influence on CA familiarity and adoption among followersthrough their motivation, familiarity, and own adoption and (b) F2FE is a complement rather than a substitute for other agricultural extension activities. Policy implications are discussed.
Keywords: Q16; 330; Africa; conservation agriculture (CA); farmer-to-farmer extension (F2FE); Malawi; technology adoption; lead farmers; followers of lead farmers